2004
DOI: 10.1002/rem.20021
|View full text |Cite
|
Sign up to set email alerts
|

Using wind to power a groundwater circulation well—preliminary results

Abstract: In areas of the country where the U.S. Department of Energy has classified the available wind resources as Class 3 or greater, the use of wind turbines to provide power to relatively small remediation systems such as groundwater circulation wells may be technically and economically feasible. Groundwater circulation wells are a good candidate technology to couple with renewable energy, because the remediation system removes contamination from the subject aquifer with no net loss of the groundwater resource, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The following equation thereby results in a simpler wind probability calculation using the more commonly available wind velocity instead of the Weibull scale value. (2) Where Γ( ) is the gamma function. The typical values of k for most wind site conditions range from 1.5 to 3.0 as found in [8] but for this paper we calculated the values for the selected…”
Section: Wind Energy Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following equation thereby results in a simpler wind probability calculation using the more commonly available wind velocity instead of the Weibull scale value. (2) Where Γ( ) is the gamma function. The typical values of k for most wind site conditions range from 1.5 to 3.0 as found in [8] but for this paper we calculated the values for the selected…”
Section: Wind Energy Calculationsmentioning
confidence: 99%
“…This paper will build on earlier work regarding the use of low cost and readily available wind velocity data from regional climate center weather stations to predict wind turbine performance. Elmore et al [2] showed that the use of a regional wind map resulted in the over estimation of energy production for a Bergey Wind Company (BWC) 10 kW wind turbine used to partially power a groundwater circulation well (GCW) system at the former Nebraska Ordnance Plant (FNOP) Superfund site. The use of regional climate center data to predict the wind velocity and wind turbine energy production at the GCW location was further explored in Gallagher and Elmore [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation